ZED1-related kinase 13 is required for resistance against Pseudoidium neolycopersici in Arabidopsis accession Bla-6 - Santillán Martínez, Miguel I.; Gao, Dongli; Appiano, Michela; Derks, Inge; Huibers, Robin P.; Spil, Glenn; Wang, Xulan; Visser, Richard G. F.; Wolters, Anne-Marie A.; Bai, Yuling (Frontiers in Plant Science, 2023)
To explore specific components of resistance against the tomato-adapted powdery mildew pathogen Pseudoidium neolycopersici (On) in the model plant Arabidopsis, we performed a disease assay in 123 accessions. When testing the resistance in the F1 from crossings between resistant accessions with susceptible Col-0 or Sha, only the progeny of the cross between accession Bla-6 and Col-0 displayed a completely resistant phenotype. The resistance in Bla-6 is known to be specific for Pseudoidium neolycopersici. QTL analysis and fine-mapping through several rounds of recombinant screenings allowed us to locate a major resistance QTL in an interval on chromosome 1, containing two candidate genes and an intergenic insertion. Via CRISPR/Cas9 targeted mutagenesis, we could show that knocking out the ZED-1 RELATED KINASE 13 (ZRK13) gene compromised the On resistance in Bla-6. Several polymorphisms are observed in the ZRK13 allelic variant of Bla-6 when compared to the Col-0 protein.